2015
DOI: 10.1108/jsit-06-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Uses and gratifications of social media: a comparison of microblog and WeChat

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 32 publications
9
118
0
8
Order By: Relevance
“…Similarly, the effect of arousal on WOM was only an indirect relationship, acting through pleasure. The unsupported relationships are all linked to the arousal construct similar to other studies that have also found difficulties with arousal responses in the mobile context (Gao, 2015, Gan, 2015 which may suggest that the mobile context is less immediately arousing that a physical retail environment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, the effect of arousal on WOM was only an indirect relationship, acting through pleasure. The unsupported relationships are all linked to the arousal construct similar to other studies that have also found difficulties with arousal responses in the mobile context (Gao, 2015, Gan, 2015 which may suggest that the mobile context is less immediately arousing that a physical retail environment.…”
Section: Discussionsupporting
confidence: 78%
“…Social aspects are critical in determining adoption of social media including smart retail channel MIM applications (Gan and Wang, 2015, Li, Chen et al, 2015, Li, Liu, et al, 2015. Studies have identified that gender is a critical moderating variable influencing adoption of social media for interpersonal communications; female respondents prefer to use social media with social interaction aspects (Kimbrough et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Digital natives may be more attractive to the open-model social media tools, such as Microblog. For example, Microblog assists young people in searching and gaining information about work, study and daily life which will in turn promote Microblog use behavior [25]. Information on close friends and social events support satisfaction with social networks and continuance intention among both young and old generation [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this theory highlights the impacts of social and psychological gratifications that shape people's motivation for using social media [24]. As per prior research, users can obtain various gratifications from using social media including content, social, process and hedonic gratification, which in turn drive their actual usage [25]. We use this theory to overarchingly guide the selection of independent variables.…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%
“…For example, WeChat is a closed social networking platform that allows users to connect with everyone in his/her circle, while strangers and the general public are not allowed to review or comment on their personal pages. In addition, WeChat embraces instant messaging with text, image, voice and video chat; these features make the social media usage by China's best hospitals unique [16]. Hospitals implementing WeChat to provide services for patients, including making appointments with physicians and distributing health Republic of China, were selected for this study.…”
Section: Introductionmentioning
confidence: 99%